Pengaruh Struktur Aset dan Pertumbuhan Penjualan Terhadap Struktur Modal dengan Risiko Bisnis Sebagai Variabel Moderating : (Studi Pada Perusahaan Terindeks LQ45 di Bursa Efek Indonesia Tahun 2015-2018) - Rizky Hermayanti; Destia Pentiana; Anita Kusuma Dewi (Jurnal Ilmiah ESAI, 2023)
The purpose of this study was to examine the effect of asset structure and sales growth on capital structure with business risk as a moderating variable by focusing on LQ45 indexed companies on Indonesia Stock Exchange in the period of 2015-2018. Capital structure was a dependent variable, while asset structure and sales growth were independent variables and business risk was a moderating variable. The sampling method used was purposive sampling with a sampel of 26 companies during the observation period of 4 years in a row to produce a tatal of 104 samples and 81 for samples after data transformation. The analysis technique used in this research used SPSS 22 version with multiple linier regresision analysis. The results of this study indicate that asset structure does not effect on capital structure, sales growth has an effect on capital structure, business risk can not moderated effect between asset structure with capital structure and business risk can moderated effect between sales growth with capital structure.